Late medieval and early modern fight books
1 online resource.
Keywords: Late Medieval and Early Modern Fight Books offers insights into the cultural and historical transmission and practices of martial arts, based on the corpus of the Fight Books (Fechtbücher) in 14th- to 17th-century Europe. The first part of the book deals with methodological and specific issues for the studies of this emerging interdisciplinary field of research. The second section offers an overview of the corpus based on geographical areas. The final part offers some relevant case studies. This is the first book proposing a comprehensive state of research and an overview of Historical European Martial Arts Studies. One of its major strengths lies in its association of interdisciplinary scholars with practitioners of martial arts. Contributors are Sydney Anglo, Matthias Johannes Bauer, Eric Burkart, Marco Cavina, Franck Cinato, John Clements, Timothy Dawson, Olivier Dupuis, Bert Gevaert, Dierk Hagedorn, Daniel Jaquet, Rachel E. Kellet, Jens Peter Kleinau, Ken Mondschein, Reinier van Noort, B. Ann Tlusty, Manuel Valle Ortiz, Karin Verelst, and Paul Wagner.